TECHNIQUES IN CONDUCTING ENGLISH READING SKILLS TEST PERFORMED BY INDONESIAN TEACHERS ON ASSESSMENT OF LOCAL EDUCATION STANDARD 2021 - Adhe Puspita Mayasari; Ani Susanti (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
One of the ways to measure the students' English reading comprehension skills is through testing. Despite its significant value, students frequently construct bad tests without considering the main rules in doing English reading comprehension tests. This research concerns to study of techniques in testing English comprehension reading skills performed by teachers in Indonesia on Assessment of Local Education Standard in the year 2021. Assessment of Local Education Standard abbreviated as ASPD in a provincial- standardized test to maintain the quality of learning. Four EFL teachers in Indonesia were chosen based on their teaching experience in high schools. The researcher used document observation and in depth- interview techniques to collect data which were transformed into observation notes and interview transcription. The data were then analyzed qualitatively. Findings from this study shown that there are three main themes regarding the most used techniques performed by the teachers, first, students must be able to analyze the bloom taxonomy theory, second, students must be able to identify the scope of material, and third determining the keywords of the question. From understanding and doing those three themes, teachers believe that these techniques could help and improve student's ability in facing English reading comprehension tests.